Relevance of DNA barcodes for biomonitoring of freshwater animals - Elías-Gutiérrez, Manuel; Valdez-Moreno, Martha (Frontiers in Environmental Science, 2023)
The COI gene, colloquially named the DNA barcode, is a universal marker for species identification in the animal kingdom. Nevertheless, due to the taxonomic impediment, there are various proposals for molecular operational taxonomic units (MOTUs) because high-throughput sequencers can generate millions of sequences in one run. In the case of freshwater systems, it is possible to analyze whole communities through their DNA using only water or sediment as a sample. Using DNA barcodes with these technologies is known as metabarcoding. More than 90% of studies based on eDNA work with MOTUs without previous knowledge of the biodiversity in the habitat. Despite this problem, it has been proposed as the future for biomonitoring. All these studies are biased toward the Global North and focused on freshwater macrofaunae. Few studies include other regions of the world or other communities, such as zooplankton and phytoplankton. The future of biomonitoring should be based on a standardized gene, for example, COI, the most studied gene in animals, or another secondary consensual gene. Here, we analyzed some proposals with 28S or 12S. The studies on eDNA can focus on analyses of the whole community or a particular species. The latter can be an endangered or exotic species. Any eDNA study focused on a community study should have a well-documented DNA baseline linked to vouchered specimens. Otherwise, it will be tough to discriminate between false positives and negatives. Biomonitoring routines based on eDNA can detect a change in a community due to any perturbation of the aquatic ecosystem. Also, it can track changes along the history of an epicontinental environment through the analyses of sediments. However, their implementation will be complex in most megadiverse Neotropical countries due to the lack of these baselines. It has been demonstrated that a rapid functional construction of a DNA baseline is possible, although the curation of the species can take more time. However, there is a lack of governmental interest in this kind of research and subsequent biomonitoring.